2008
DOI: 10.2967/jnumed.108.050484
|View full text |Cite
|
Sign up to set email alerts
|

Gated Myocardial Perfusion SPECT: Algorithm-Specific Influence of Reorientation on Calculation of Left Ventricular Volumes and Ejection Fraction

Abstract: Gated myocardial perfusion SPECT allows calculation of enddiastolic and end-systolic volumes (EDV and ESV, respectively) and left ventricular ejection fraction (LVEF). The quantification algorithms QGS (quantitative gated SPECT), 4D-MSPECT, and CARE heart show a good correlation with cardiac MRI. Nevertheless, differences in contour finding suggest algorithm-specific effects if heart axes vary. The effect of tilting heart axes on gated SPECT was quantified as a possible source of error. Methods: Sixty men un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Differences in the algorithms for definition of endocardial and epicardial borders and definition of the base and valve planes are the most likely explanation for this observation. For example, QGS uses a 3-dimensional model of the heart without specific geometric assumptions of horizontal or transversal long axes, ECTb uses a 2-coordinate system (cylindric coordinate for basal and mid-myocardial segments but spheric coordinate for the apex), and 4DM requires the heart base to be perpendicular to the chosen long axes (21). Moreover, ECTb and QGS valve-plane definition models assume that the septal wall is shorter than the lateral wall; consequently, the basal limits are independently estimated on each side of the left ventricle, whereas 4DM assumes that the basal limits are the same in the septal and lateral walls (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the algorithms for definition of endocardial and epicardial borders and definition of the base and valve planes are the most likely explanation for this observation. For example, QGS uses a 3-dimensional model of the heart without specific geometric assumptions of horizontal or transversal long axes, ECTb uses a 2-coordinate system (cylindric coordinate for basal and mid-myocardial segments but spheric coordinate for the apex), and 4DM requires the heart base to be perpendicular to the chosen long axes (21). Moreover, ECTb and QGS valve-plane definition models assume that the septal wall is shorter than the lateral wall; consequently, the basal limits are independently estimated on each side of the left ventricle, whereas 4DM assumes that the basal limits are the same in the septal and lateral walls (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…This concept was tested in a large population (984 patients), whose stress and rest gated SPECT studies underwent the same 15 degrees change in reorientation angles during processing as described above for Knollman’s data (2). The results of paired processing and quantification are shown in Table 2, and demonstrate a very substantial improvement in Δrepro.…”
Section: Can We Do Better?mentioning
confidence: 99%
“…For example, a paper by Knollman et al investigated the variation in quantitative LV function measurements resulting from a simple 15 degrees change in the reorientation angles during processing of 59 gated SPECT datasets. The patient population comprised a good range of LVEFs (20%–80%) end-systolic volumes (ESVs) and end-diastolic volumes (EDVs), which were quantified using three different software algorithms - and while correlation coefficients were generally high, the most reproducible algorithm still produced differences of 2.8%, 7.5ml and 9ml for LVEF, ESV and EDV, respectively, at the 95% confidence interval level (2). In layman’s terms, 5% of the time one should expect quantitative differences greater than those listed above as a consequence of just altering the reorientation angle by 15 degrees during reconstruction.…”
mentioning
confidence: 99%
“…For example, increasing zoom factor or changing filter type or changing cut-off value in butter worth filter. However, the use of these applications in routine is not practical and it has been reported that EF values were overestimated in these studies, as well 18 .…”
Section: Cmjmentioning
confidence: 99%